Small hydropower plants and livelihoods of the local population in rural Vietnam. - Eva Seewald; Ulrike Grote; Trung Thanh Nguyen (PLoS ONE)
In the past decades, Vietnam has witnessed a great expansion of small hydropower plants (HPPs) to meet the rapidly increasing demand for electricity, improve access to water and protect against droughts. However, it is far from clear whether HPPs have exclusively positive impacts on the surrounding population as they are often accompanied by competition for natural resources (e.g., land). Therefore, this analysis investigates the impact of small HPPs on the livelihoods of the surrounding population. To this end, a unique large dataset of 2,195 rural Vietnamese households from a socioeconomic panel is combined with spatial data on HPPs. Results from fixed effects panel regressions show positive effects of HPPs on agricultural income, irrigated cropland, and the number of expected droughts. However, the effects differ depending on the location of the local population. While the downstream population benefits, the upstream population does not appear to benefit. Policymakers should, therefore, be aware of the diverse impacts in order to take effective measures and avoid social conflicts in rural Vietnam.